2015
DOI: 10.1523/eneuro.0016-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Src Is Associated with Phenotypes Related to Williams-Beuren Syndrome and Altered Cellular Localization of TFII-I

Abstract: Src tyrosine kinase phosphorylates the general transcription factor protein TFII-I, which is deleted in the neurodevelopmental disorder Williams-Beuren syndrome (WBS). We identified phenotypes such as increased sociability, visuospatial deficits, craniofacial abnormalities, and hyperactivity that overlap with symptoms of WBS in a mouse with disruption of Src.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…CD animals fed with EGCG presented normalized expression levels of Bdnf without any effect in neuroanatomical remodeling. It has been shown that the membrane localization of TRPC3 channels, important mediators of BDNF-mediated Ca 2+ signal generation and dendritic remodeling [ 46 ], is regulated by general transcription factor TFII-I encoded by GTF2I deleted in WBS[ 33 , 34 ]. In hippocampal primary cultures of CD mice we observed altered intracellular calcium flux although no significant changes in TRPC3 distribution were observed.…”
Section: Discussionmentioning
confidence: 99%
“…CD animals fed with EGCG presented normalized expression levels of Bdnf without any effect in neuroanatomical remodeling. It has been shown that the membrane localization of TRPC3 channels, important mediators of BDNF-mediated Ca 2+ signal generation and dendritic remodeling [ 46 ], is regulated by general transcription factor TFII-I encoded by GTF2I deleted in WBS[ 33 , 34 ]. In hippocampal primary cultures of CD mice we observed altered intracellular calcium flux although no significant changes in TRPC3 distribution were observed.…”
Section: Discussionmentioning
confidence: 99%
“…4D ) ( 66 ). In order to assess whether the phosphorylation seen in TFII-I is observed in GTF2IRD1, reported phosphorylation sites in TFII-I were searched for in GTF2IRD1 ( 67 69 ). TFII-I contained two consensus Src-dependent tyrosine phosphorylation sites with two additional Src homology-binding motifs ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle tension was measured by grip strength test described previously with minor modifications ( 42 ). Briefly, grip strength was measured by recording latency of time the mouse was able to hold on a steel wire (9.0 mm in diameter, 50.0 mm in length) suspended 40.0 cm above the horizontal surface of the ground.…”
Section: Methodsmentioning
confidence: 99%